Patient-reported sexual function of breast cancer survivors with genitourinary syndrome of menopause after fractional CO2 laser therapy. Issue 6 (June 2021) - Quick, Allison M.; Zvinovski, Filadelfiya; Hudson, Catherine; Hundley, Andrew; Evans, Cynthia; Stephens, Julie A.; Arthur, Elizabeth; Ramaswamy, Bhuvaneswari; Reinbolt, Raquel E.; Noonan, Anne M.; VanDeusen, Jeffrey Bryan; Wesolowski, Robert; et al.
Abstract: Objective: The objective of this pilot study was to evaluate the change in sexual function following treatment with fractional CO2 laser therapy in breast cancer (BC) survivors with genitourinary syndrome of menopause (GSM). Methods: A single-arm feasibility study of BC survivors with symptoms of GSM, including dyspareunia and/or vaginal dryness, was conducted. Participants who received three treatments with fractional CO2 laser and 4-week follow-up were contacted for patient-reported outcomes and adverse events at 12 months. Sexual function was measured using the Female Sexual Function Index (FSFI) and Female Sexual Distress Scale Revised (FSDS-R). Descriptive statistics were calculated for patient demographics and disease characteristics for the set of participants who agreed to long-term follow-up and those who were lost to follow-up. FSFI and FSDS-R scores were summarized at baseline, 4 weeks and 12 months, as well as the change from baseline, and were compared using a Wilcoxon signed rank test. Results: A total of 67 BC survivors enrolled, 59 completed treatments and 4-week follow-up; 39 participated in the 12 month follow-up. The overall FSFI score improved from baseline to 4-week follow-up (median Δ 8.8 [Q1, Q3] (QS) (2.2, 16.7)], P  < 0.001). There were improvements at 4 weeks in all domains of the FSFI ( P  < 0.001 for each) including desire (median Δ 1.2; QS [0.6, 1.8]), arousal (median Δ 1.2; QS [0.3, 2.7]), lubrication (median Δ 1.8 (0, 3.3), orgasm (median Δ 1.2; QS [0, 3.6]), satisfaction (median Δ 1.6 (0.4, 3.2)), and pain (median Δ 1.6 (0, 3.6). The FSDS-R score also improved from baseline to 4-week follow-up (median Δ −10.0; QS [−16, −5] P  < 0.001) indicating less sexually related distress. The scores of the FSFI and FSDS-R remained improved at 12 months and there were no serious adverse events reported. Conclusions: In BC survivors with GSM, the total and individual domain scores of the FSFI and the FSDS-R improved after fractional CO2 laser therapy. N/A: Video Summary: http://links.lww.com/MENO/A711 . Abstract : Supplemental Digital Content is available in the text